The Potential of Natural Daylight Utilization for the Visual Comfort of Occupants in Two Units of Service Apartments Certified as Green Buildings in Kuala Lumpur, Malaysia - Suriansyah, Yasmin (International Journal of Integrated Engineering, 2020)
Visual comfort is one of the most salient aspects of the architectural design of a residential unit. This paper is the result of a research on the visual comfort evaluations made in two residential units, in service apartments certified as green buildings in Kuala Lumpur, Malaysia. The analysis focuses on evaluating visual comfort based on three matters. The first, a simulation of lighting levels or illuminance value in residential units, using Dialux version 4.12 software. The second, the results of actual measurements of the level of illumination inside the residential unit, using a lux-meter measuring instrument. The third, visual perceptions and preferences of the users of the AU as respondents through a brief interview. The results show that the potential for using natural lighting for the visual comfort of apartment users can only fulfill the bedroom, and the sitting room, while other spaces must still rely on artificial light. This situation relates to the influence of the spatial design of space settings in residential units. The results of the research are essential for all parties involved in architectural design, management, and users of residential units in service apartments certified as a green building.